Preference in learning styles and understanding of semantic relationships of the text - Gamero Guillén, Ana María (2023)
The objective of this research was to establish the relationship between the understanding of semantic relationships and the level of preference in learning styles. A non-experimental descriptive correlational design is used, the data collection instruments were the CHAEA and the ECLE-3, the sample consisted of 134 first grade high school students. The results indicate that there is a significant (p<0.01) and weak (rho=0.334) relationship between the understanding of semantic relationships and the level of preference of the reflective style, as well as a significant (p<0.01) and weak (rho=0.188) relationship between the understanding of semantic relations and the level of preference of theoretical style.